问题 解答题
脱式计算
1
16
+
1
2
×
5
8
-
1
3

1
2
+(
3
4
-
1
12
)×
3
5

③(
7
9
-
5
18
)×(
3
4
+
5
8
④(
1
6
×
3
8
)×24
⑤45×
4
9
-
4
9
×45
⑥27×
4
5
+27÷5.
答案

1
16
+
1
2
×
5
8
-
1
3

=

1
16
+
5
16
-
1
3

=

3
8
-
1
3

=

1
24

1
2
+(
3
4
-
1
12
)×
3
5

=

1
2
+
2
3
×
3
5

=

1
2
+
2
5

=

9
10

③(

7
9
-
5
18
)×(
3
4
+
5
8
),

=

1
2
×
11
8

=

11
16

④(

1
6
×
3
8
)×24,

=

1
16
×24,

=

3
2

⑤45×

4
9
-
4
9
×45,

=(45-45)×

4
9

=0×

4
9

=0;

⑥27×

4
5
+27÷5,

=27×

4
5
+27×
1
5

=27×(

4
5
+
1
5
),

=27×1,

=27.

单项选择题 A1型题
单项选择题